Impact of Macro Specific Factor and Bank Specific Factor on Bank Liquidity using FMOLS Approach - Mahmood, Hamid; Khalid, Samia; Waheed, Abdul; Arif, Muhammad (Ital Publication, 2019)
By applying the fully modified ordinary least square (FMOLS), this study examines the impact of bank-specific factor and macro-specific factors on bank liquidity, for the period of 2000 to 2017. The bank specific factors include bank crises, bank size, total deposit, and profitability. While it considers a macro-specific factors GDP, inflation, monetary policy and unemployment. Findings reveal that based on time series data, we suggest that bank-specific and macro-specific factor significantly effect on bank liquidity. Empirical results reported that at 5 percent level of significance total deposit, GDP, bank size and unemployment have a negative impact on liquidity of the bank. While monetary policy, bank crisis and profitability have a positive impact on liquidity. Inflation has an insignificant relation with liquidity. The study reported new facts for increase more clear understanding of liquidity in a developing country like Pakistan.